Digitalization, AI Adoption, and MSME Productivity: An Ibn Khaldunian Perspective - Feriandy Feriandy (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face persistent challenges in improving labor productivity amid rapid digital transformation and the expansion of artificial intelligence (AI). Although digitalization has increased substantially, its productivity effects remain uneven across provinces and are influenced by institutional, cultural, and religious contexts. Grounded in Ibn Khaldun’s concepts of asabiyyah and tadbir al-‘umran, this study examines the relationship between digitalization, AI adoption, and MSME labor productivity while assessing the moderating role of religiosity. The study employs an explanatory quantitative approach using provincial-level panel data during 2020–2023. The primary estimation uses a fixed-effects model with robust standard errors, complemented by exploratory analyses using Double Machine Learning, Causal Forest, and XGBoost. The findings show that digitalization has a positive and significant effect on labor productivity, whereas AI adoption has not yet generated measurable productivity gains. Religiosity marginally weakens the relationship between digitalization and productivity, indicating transitional adaptation frictions within highly normative environments rather than resistance to technology. These findings suggest that sustainable productivity gains depend not only on technological adoption, but also on institutional capacity, ethical governance, and collective learning mechanisms. The study contributes to the digital transformation literature by extending Ibn Khaldun’s institutional perspective and offers policy insights for strengthening sustainable MSME digital ecosystems in Indonesia. ABSTRAK - Digitalisasi, Adopsi AI, dan Produktivitas UMKM: Perspektif Ibn Khaldun. Usaha Mikro, Kecil, dan Menengah (UMKM) di Indonesia menghadapi tantangan dalam meningkatkan produktivitas tenaga kerja di tengah percepatan transformasi digital dan perkembangan kecerdasan buatan (artificial intelligence/AI). Meskipun digitalisasi berkembang pesat, dampaknya terhadap produktivitas masih berbeda antarprovinsi dan dipengaruhi oleh faktor institusional, budaya, dan religiositas. Berlandaskan konsep asabiyyah dan tadbir al-‘umran dari Ibn Khaldun, penelitian ini menganalisis hubungan antara digitalisasi, adopsi AI, dan produktivitas tenaga kerja UMKM serta menguji peran moderasi religiositas. Penelitian menggunakan pendekatan kuantitatif eksplanatori dengan data panel tingkat provinsi selama periode 2020–2023. Estimasi utama dilakukan melalui model fixed effects dengan robust standard errors dan dilengkapi analisis eksploratif menggunakan Double Machine Learning, Causal Forest, dan XGBoost. Hasil penelitian menunjukkan bahwa digitalisasi berpengaruh positif dan signifikan terhadap produktivitas tenaga kerja, sedangkan adopsi AI belum menunjukkan dampak yang signifikan. Religiositas memoderasi hubungan digitalisasi dan produktivitas secara negatif marginal, yang mencerminkan friksi adaptasi dalam lingkungan dengan kohesi normatif tinggi, bukan penolakan terhadap teknologi. Temuan ini menunjukkan bahwa keberhasilan transformasi digital bergantung pada kapasitas kelembagaan, tata kelola etis, dan mekanisme pembelajaran kolektif. Studi ini memperluas perspektif institusional Ibn Khaldun dalam kajian transformasi digital serta memberikan implikasi kebijakan bagi penguatan ekosistem digital UMKM yang berkelanjutan di Indonesia.